Theoretical and experimental analysis of elastic–plastic cylindrical shells under two types of axial impacts. (October 2016) - Rajabiehfard, R.; Darvizeh, A.; Darvizeh, M.; Ansari, R.; Alitavoli, M.; Sadeghi, H.
Abstract: In this paper, the dynamic buckling of axisymmetric circular cylindrical shells subjected to axial impact is investigated theoretically and experimentally. The von Mises yield criterion is used for the elastic–plastic cylindrical shell made of linear strain hardening material in order to derive the constitutive relations between stress and strain increments. Nonlinear dynamic circular cylindrical shell equations are solved with using finite difference method for two types of loading which are stationary cylindrical shells impacted axially and traveling cylindrical shells impacted against a rigid wall. Experimental tests for two types of loading are performed by gas gun. Theoretical and experimental results for cylindrical shells under axial impact for different loading conditions are reported and it is found that there is a good agreement between them. Highlights: Nonlinear axisymmetric dynamic circular cylindrical shell equations are derived and solved with finite difference method for two types of loading. Experimental tests for two types of loading are performed by gas gun. Experimental and theoretical shortening, energy absorption, half-wave number, buckling shape and peak load are compared with each other.